Expérimenter l’ambiance par l’architecture - Grégoire Chelkoff (Ambiances)
Experiencing on ambiance with architecture questions both the research methods on ambiances and the role of architecture in their advent. Several approaches can be explored to determine the conditions that allow to implement experiments within research, providing new knowledge and new ways of action, expression and dissemination. This is the question of this issue.